2016
DOI: 10.1080/02626667.2014.932911
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hydrological and climatic variables affected by four variations of the Mann-Kendall approach in Urmia Lake basin, Iran

Abstract: The trends in hydrological and climatic time series data of Urmia Lake basin in Iran were examined using the four different versions of the Mann-Kendall (MK) approach: (i) the original MK test; (ii) the MK test considering the effect of lag-1 autocorrelation; (iii) the MK test considering the effect of all autocorrelation or sample size; and (iv) the MK test considering the Hurst coefficient. Identification of hydrological and climatic data trends was carried out at monthly and annual time scales for 25 temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 30 publications
2
44
0
1
Order By: Relevance
“…A number of recent studies have revealed the difference in trends obtained using the MK and MMK tests due to LTP (Kumar et al, ; Shahid et al, ; Fathian et al, ; Khan et al , 2018a). The large difference in the number of significant trends in rainfall indices obtained in this study using the MK and MMK tests indicates that the significant changes estimated by the MK test at many grid points in Peninsular Malaysia may be due to the lack of consideration of LTP in time series during trend analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have revealed the difference in trends obtained using the MK and MMK tests due to LTP (Kumar et al, ; Shahid et al, ; Fathian et al, ; Khan et al , 2018a). The large difference in the number of significant trends in rainfall indices obtained in this study using the MK and MMK tests indicates that the significant changes estimated by the MK test at many grid points in Peninsular Malaysia may be due to the lack of consideration of LTP in time series during trend analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The rank-based non-parametric Mann-Kendall statistical test [38] is commonly used for trend detection due to its robustness for non-normally distributed data, hence it is frequently applied to hydro-climatic time series [39,40]. Assuming a normal distribution at the significant level of p = 0.05, a positive Mann-Kendall statistic Z larger than 1.96 indicates an significant increasing trend, whereas a negative Z lower than −1.96 indicates a significant decreasing trend.…”
Section: Methodsmentioning
confidence: 99%
“…The MK test is a nonparametric statistical test (Mann, 1945;Kendall and Charles, 1975) that is useful for assessing the significance of trends in time series data (Waked et al, 2016;Fathian et al, 2016). The MK test is often used to detect a step change point in the long-term trend of a time series dataset (Moraes et al, 1998;Li et al, 2016;Zhao et al, 2015).…”
Section: Trends and Step Changementioning
confidence: 99%